1999
DOI: 10.1046/j.1365-2745.1999.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Hedgerows as habitat corridors for forest herbs in central New York, USA

Abstract: Summary 0 Samples from 21 hedgerows "c[ 5 m wide\ with full!grown trees# in central New York included 28 forest herb taxa\ comprising nearly 69) of the forest herb taxa found in adjacent forest samples[ 1 We sampled three types of hedgerow[ Two types were attached to forest] remnant hedgerows "n 03#\ and regenerated hedgerows "n 00# that had grown up spon! taneously between open _elds in the last 49 years[ There were no signi_cant di}erences between remnant and regenerated hedgerows in the richness or abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 31 publications
(57 reference statements)
7
85
0
1
Order By: Relevance
“…This observation is in accordance with the surveys conducted in other geographical regions, where road verges offer alternative habitats, for example for 70% of forest herbs in the USA [46] and for 80% of grassland flora in Central Europe [47]. In Poland, railway embankments have been recognized as refuge areas for ca.…”
Section: Factors Affecting Flowering Plants -Railway Embankments Vs supporting
confidence: 88%
“…This observation is in accordance with the surveys conducted in other geographical regions, where road verges offer alternative habitats, for example for 70% of forest herbs in the USA [46] and for 80% of grassland flora in Central Europe [47]. In Poland, railway embankments have been recognized as refuge areas for ca.…”
Section: Factors Affecting Flowering Plants -Railway Embankments Vs supporting
confidence: 88%
“…It may be that restoration work is needed in these hedgerows in order to improve species diversity, especially in those areas where woodlands are not present in the vicinity and where seeds are unlikely to reach these habitats. The ecological environment around any hedgerows/field margins also influences the composition of species due to dispersal of seeds by wind or animals or colonisation from nearby woodlots (Corbit et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Boundary type, which was also found to be a significant factor, can influence vegetation in a variety of ways, acting as a physical barrier to ungulate movement or, in the case of hedges, acting as refugia (McCollin et al 2000;Smart et al 2001) or dispersal pathways for forest herb species, as demonstrated in central New York, USA (Corbit et al 1999). Adjacent water bodies such as streams and rivers aid dispersal of both terrestrial and riparian plant species (e.g.…”
Section: - mentioning
confidence: 99%